Menilik Implementasi Quick Response Dalam Mewujudkan Keamanan Di Polres Jembrana - Rahman, Supriadi; Mahyuni, Luh Putu (Penerbit STKIP PGRI Bangkalan, 2021)
Polres as a basic operational unit, has a complete police function to solve all police problems, which can provide complete solutions to the community. The National Police Headquarters set four excellent programs as quick wins in implementing bureaucratic reform: quick response of the Samapta patrol, transparency of SIM, STNK and BPKB services, transparency of investigative services (SP2HD), and transparency in the recruitment of Police personnel. This study aims to determine the form of police activities that implement the Quick Response program and to find out the mechanism for filing claims by the community to the Jembrana Police for police officers who do not implement the Quick Response. The technique used in processing data is descriptive qualitative using data analysis techniques proposed by Huberman. The results of the research stated that, there were still findings from one of the informants who stated that there was a slow case resolution and was not informed to the reporter, there were still many people who did not know the Jembrana Police jurisdiction and during the patrol implementation of Jembrana Police members only went around the city area. The contribution of this research is to provide insight to the public regarding the performance of quick response in Jembrana Police.